Pengaruh Elemen Fraud Hexagon Terhadap Kecurangan Laporan Keuangan - Maharani, Farida; Napisah, Napisah (Politeknik Ganesha Medan, 2024)
This research aims to determine the influence of External Pressure, Ineffective Monitoring, Total Accrual Ratio, Change Of Directors, Frequent Number Of CEO'S Picture, and Pokitical Connection Fraud hexagon elements on the condition of financial statements. This study uses a population of Kompas 100 companies listed on the Indonesia Stock Exchange in the period 2018 - 2022 The number of samples used was 43 companies from the purposive sampling method using 2 sample criteria. The data analysis method used in this study is a panel data regression model processed using eviews 12. The results of this study indicate that out of all independent variables, there are 2 variables that influence financial statement fraud, namely the Stimulus variable with the proxy of External Pressure with a probability value of 0.0000 and the Opportunity variable with the proxy of Ineffective Supervision with a probability value of 0.0044. Meanwhile, there are 4 variables that do not influence financial statement fraud, namely the Rationalization variable with the proxy of Total Accrual Ratio with a probability value of 0.5914, the Ability variable with the proxy of Changes in the Board of Directors with a probability value of 0.4331, the Ego variable with the proxy of the Number of CEO Photos that appear with a probability value of 0.5482, and the Collusion variable with the proxy of Political Connections with a probability value of 0.9762. The results of this study are expected to be new knowledge that can be used to determine what factors trigger financial statement fraud and can be used to anticipate financial statement fraud. The components of the fraud hexagon theory applied to Kompas100 can influence only two aspects; the other four elements cannot represent the ability to detect fraud. This can be identified because the top 100 companies are those that are relatively free from fraud.